Perceived impact of lifelong training in teachers - Jardim, Jacinto; Pereira, Anabela (Revista Interacções, 2017)
Teachers need lifelong training in the realm of soft skills. Accordingly, several training programs have been proposed for developing teachers’ personal and social skills, though they are seldom evaluated. This study proposes to present data on the subjective evaluation of the outcomes of such programs, in relation to gender, age level of teaching, and training program. A sample of 92 participants was voluntarily enrolled in one of seven training programs, and their personal change was assessed in relation to their pre and post intervention perceptions. Results indicate that all participants (irrespective of their gender, age, level of teaching or training program they attended) perceived themselves as more able after the training. This establishes the importance of such type of lifelong training being implemented as a regular option for teachers, as it may contribute to a more positive self-perception, which in turn may contribute to improved professional performance.